Financial Technology and Performance of Listed Small and Medium Scale Enterprises In Nigeria (International Journal of Scientific Research and Management (IJSRM), 2024)
Despite the unique role expected to be played by small and medium scale enterprises in every economy and Nigeria inclusive. The contribution of SME’s to economic growth and development is still retarding, which could be due to two major reasons which are intrinsic/ controllable factors and extrinsic/uncontrollable factors. This study examined the impact of financial technology on small and medium scale enterprises performance in Nigeria. The ex-post factor research design was employed. The secondary data was sourced from the audited financial statement of the small and medium scale enterprises and Central Bank Statistical Bulleting from 2019 to 2023. The ordinary least square regression was employed to determine the relationship between return on equity, sales growth and automated teller machine, web-pay, mobile money payment. The findings reveals that automated teller machine and point-of-sale has negative significant effect on return on equity (β: -1.78; t:-0.11) and (β: -0.75; t:-0.08). Also, web-pay and point of sale has negative significant effect on sales growth at (β: -0.05; t: -0.61) and (β: -1.11; t: -0.40) while mobile money payment has positive significant effect on sales growth (β: 0.65; t: 0.30). It is therefore recommended that SME’s should consider optimizing their electronic payment systems, focusing on cost-reduction strategies and enhancing the efficiency of ATM, web pay, and POS channels. Additionally, exploring alternative payment solutions or investing in technology upgrades to streamline transaction processes may mitigate the negative impact on profitability, helping firms to better align these systems with their financial objectives.